PELATIHAN GENERATIVE AI SEBAGAI PENINGKATAN KOMPETENSI MAHASISWA DALAM PENYUSUNAN PUBLIKASI ILMIAH - Muhammad Arif Rakhman; Nurmiyati, Nurmiyati; Khasanah, Uswatun (Tahta Media Grup, 2024)
In the rapidly growing digital era, the utilization of Artificial Intelligence (AI) has become increasingly essential, especially in the academic field. Generative AI is one such technology with great potential to assist in the preparation of scientific publications, particularly for students. However, students' understanding and skills in using this technology remain limited. Therefore, this study aims to evaluate the effectiveness of Generative AI training in enhancing students' competence in preparing scientific publications. The methods used include needs identification, training module design, training implementation, and evaluation with feedback from participants. The results show that after participating in the training, students' understanding of Generative AI concepts increased by 35%. Additionally, 85% of participants felt that Generative AI was highly helpful in preparing scientific publications, particularly in writing abstracts, introductions, and discussions. However, challenges remain regarding information validation and the ethical use of the technology. Based on the results, it can be concluded that Generative AI training significantly benefits students in enhancing their competence in preparing scientific publications. For further optimization, it is necessary to integrate the training into the academic curriculum and increase students' understanding of the ethics of using this technology so that they can use it responsibly.